Study on fetomaternal outcome in short interpregnancy interval: case control study - Lewis, Preeti; Mor, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study was carried out at a tertiary health centre with the aim of studying the effect of short interpregnancy interval on fetomaternal outcome. The maternal complications and fetal complications of short interpregnancy interval were analysed in comparison to normal interpregnancy interval. Methods: This is a case control study. 125 women with short interpregnancy interval seeking healthcare at tertiary health care centre were matched with 125 women with normal interpregnancy interval on the basis of demographic characteristics like age, height, weight and socio-economic status. These were included in the case control study. Results: Short interpregnancy interval is associated with increased risk of anemia, premature rupture of membranes (PROM), scar dehiscence and low birth weight whereas normal interpregnancy interval is associated with increased risk of PIH as compared to short interpregnancy interval. Conclusions: Short interpregnancy interval is associated with increased risk of anemia, PROM, scar dehiscence and low birth weight whereas normal interpregnancy interval is associated with increased risk of PIH.